Alpha band frontal connectivity is a state-specific electroencephalographic correlate of unresponsiveness during exposure to dexmedetomidine and propofol - Roosa E. Kallionpää; Katja Valli; Annalotta Scheinin; Jaakko Långsjö; Anu Maksimow; Tero Vahlberg; Antti Revonsuo; Harry Scheinin; George A. Mashour; Duan Li (ELSEVIER SCI LTD, 2022)
Background: Coherent alpha electroencephalogram (EEG) rhythms in the frontal cortex have been correlated with the hypnotic effects of propofol and dexmedetomidine, but less is known about frontal connectivity as a state-specific correlate of unresponsiveness as compared with long-range connectivity. We aimed to distinguish dose- and state-dependent effects of dexmedetomidine and propofol on EEG connectivity.
Methods: Forty-seven healthy males received either dexmedetomidine (n=23) or propofol (n =24) as target-controlled infusion with stepwise increments until loss of responsiveness (LOR). We attempted to arouse participants during constant dosing (return of responsiveness [ROR]), and the target concentration was then increased 50% to achieve presumed loss of consciousness. We collected 64-channel EEG data and prefrontal-frontal and anterior-posterior functional connectivity in the alpha band (8-14 Hz) was measured using coherence and weighted phase lag index (wPLI). Directed connectivity was measured with directed phase lag index (dPLI).
Results: Prefrontal-frontal EEG-based connectivity discriminated the states at the different drug concentrations. At ROR, prefrontal-frontal connectivity reversed to the level observed before LOR, indicating that connectivity changes were related to unresponsiveness rather than drug concentration. Unresponsiveness was associated with emergence of frontal-to-prefrontal dominance (dPLI: -0.13 to -0.40) in contrast to baseline (dPLI: 0.01-0.02). Coherence, wPLI, and dPLI had similar capability to discriminate the states that differed in terms of responsiveness and drug concentration. In contrast, anterior-posterior connectivity in the alpha band did not differentiate LOR and ROR.
Conclusions: Local prefrontal-frontal EEG-based connectivity reflects unresponsiveness induced by propofol or dexmedetomidine, suggesting its utility in monitoring the anaesthetised state with these agents.
Clinical trial registration:NCT01889004